Going places - Reynolds, Peter H. (Peter Hamilton), 1961- (Atheneum Books for Young Readers, 2014)
Rafael has looked forward to the Going Places contest and builds his go-cart from a kit in record time, but his neighbor, Maya, has a much more interesting and creative idea for her entry and Rafael decides to help.